Controlador de carga MPPT con método de estimación del estado de carga basado en conteo de amperios hora y voltaje a circuito abierto - Bustos-Márquez, Luis Fernando; Sepúlveda-Mora, Sergio Basilio; Guevara-Ibarra, Dinael; Medina-Delgado, Byron (Ingeniería, 2023)
Context: Off-grid photovoltaic systems are one of the main alternatives to fulfill the need for electricity in rural areas where the connection to traditional electrification systems is not possible. Among the components of a photovoltaic off-grid system, the charge controller must adapt the voltage and current levels to store the energy delivered by the panels in batteries. Method: In this work, a maximum power point tracking (MPPT) charge controller based on the Perturbation and Observation (P&O) technique was implemented and evaluated. Additionally, the state of charge of the battery was estimated by combining the ampere-hour counting method and the open-circuit voltage. The controller implements a two-phase charging algorithm for lead-acid batteries. Results: The developed charge controller obtained an average efficiency of 84,7% and reached a maximum value of 96,3%. In addition, the two-phase charging algorithm and the state of charge estimation method implemented in the controller allowed for the adequate control and monitoring of the battery charging and discharging processes. ConConclusions: The proposed charge controller follows the maximum power point of the solar panel and allows storing energy in lead-acid batteries while supervising their state of charge.